Assessment reliability parameters of the DVB-T2 broadcasting station’s equipment with local content insertion - S. V. Sai; N. Yu. Sorokin; О. V. Tissen (Российский технологический журнал, 2021)
Local content modification provided to subscribers of the terrestrial digital television signal is necessary to provide the technical possibility of organizing inserts of local content signals, such as TV programs of regional broadcasters, as well as information on emergency situations. Broadcast multiplexes of federal TV programs are designed for use within the corresponding time zone (A, B, C, D, M). In each time zone, there are a number of regions, in each of which there are local TV and radio companies that produce local content that must be delivered to the subscribers of the whole subject. The task of embedding/modifying content at each remote transmitting station is performed by an inserter or local content insertion device (ETSI TS 102773). The reliability parameters of the restorable system for organizing terrestrial television broadcasting at a remote station with the content modification were calculated in this article. Tables and a graph of the broadcasting system states are presented, on the basis of which, systems of Kolmogorov differential equations are compiled. It was found that additional redundancy organized by connecting the output stream from the RX1 receiver directly to the transmitting device allows for a 2.5-fold increase in the average operating time between failures, as well as an increase in the availability factor by 5.26 percent. All calculations were performed using the SimInTech software package. The influence of automatic redundancy of the local content inserter and the transmitter on the occurrence of errors in the stream that affect the quality of the output signal is considered. The relationship between the availability factor and the components of the quality of service parameter – SAE, SDE and SIE is determined.